The Profile of the European Entrepreneur: Economics and Finance, a Gender Analysis - de los Ríos Sastre, Susana; Rodríguez, F.R.; González Sánchez, Víctor M. (Springer (NY, Estados Unidos de América))
--

The role played by entrepreneurship in a country s economy is crucial, since its potential catalyzes job creation, economic growth and social impact. Case studies developed on the behaviour pattern and characteristics of the European entrepreneurship, distinguishing between male and female entrepreneurs, show that, today, gender gaps remain persistent. Progress, though, has been achieved in key areas related to gender equality between men and women. Given this context, the primary purpose of this chapter is to implement an approach to the profile of current European entrepreneurs, analyzing the main defining features, through their contribution to the European economy. Specifically, part of the chapter focuses on the study of the potential distinguishing traits of both male and female entrepreneurs in the European Union, with regard to aspects such as employment, education, activity sectors or access to finance, in comparison with other reference countries.
Capítulos en libros